ANALISIS KOMUNIKASI POLITIK DONY AHMAD MUNIR MELALUI INSTAGRAM DALAM PILKADA KABUPATEN SUMEDANG 2024 - Ripal Erlangga; Cecep Safa’atul Barkah; Tetty Herawaty; Lina Aulina (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
When someone advances as a candidate in an election, of course they will carry out a series of political activities including political campaigns, political marketing, and political communication which in this era already use social media to help carry out these activities. This year there was also a simultaneous regional election in Indonesia, one of which occurred in Sumedang Regency, which when viewed from the results of a survey conducted by a survey institution showed that candidate pair number 2, namely Dony - Fajar, had high electability far surpassing other pairs, on the other hand, candidate for regent number two, namely Dony Ahmad Munir, has an Instagram account with many followers and many uploads. From this phenomenon, researchers are interested in researching it. Therefore, the purpose of this study is to analyze political communication based on the content of Dony Ahmad Munir's uploads on Instagram. To carry out the research, the appropriate approach and finally used was descriptive qualitative with secondary data used as the main data, and the data collection technique was carried out by means of observation, Literature Study, and Documentation Study. The results of this study indicate that Instagram @ donyahmad.munir has 160 uploads from the range determined by communication and its types are divided into two categories, namely Public / Political Stories and Personal / Private Stories. Where from all the uploads, more are in the political Stories category which explains about his campaign activities and campaign information such as work programs and for the Private Stories category, he only uploads a little content, because he focuses more on campaign uploads